Evolution of the IMU Model for Evaluating the Efficiency of the Bank Computer Information Systems for Credit Risk - Kirilov, Rosen (Research Papers, 2006)
The material presents the problems in evaluating the efficiency of the bank computer information systems for credit risk. It’s based on the so called IMU model for this efficiency evaluation. The classical grade of efficiency of this specific software is based on:- using methodology for evaluating credit risk- information technologies for realization of the evaluation system- the user aspect of the efficiencyThe project describes and analyzes the changes in the process of bank crediting worldwide with a series of examples. Mainly it presents the external organizations evaluating bank credit risk – the rating agencies. In the process of this scientific research we came to the conclusion that in the future the role of those agencies in Bulgaria and around the world is growing. That’s the reason why the process of crediting is strongly determined by the credit maximum rating agencies determine. Even more important is the role of the new bank standards, such as Basel II. The project shows a number of issues: the integration of bank systems, the interaction between the information systems in the bank area and some of the services of the E-Government project. It also shows the role of the rapidly-growing usage of the electronic certificates for on-line banking and electronic credit certificates.